2016
DOI: 10.21649/akemu.v22i3.1406
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hydrotubation in Unexplained Infertility – A Randomized Controlled Trial

Abstract: <p>Unexplained infertility is a major gynecological problem with complex etiolgy. Partial tubal blockage with inflammatory reaction and thick mucus plugs in fallopian tubes and cervix is one of the likely causes in such cases. This study is based on the hypothesis that women having unexplained infertility could be helped by transcervical flushing of fluid through the fallopian tubes which would remove reversible blocking factors and help in achieving pregnancy.</p><p><strong>Objective:&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
(35 reference statements)
4
0
0
Order By: Relevance
“…One patient of ureteric fistula was managed by passing DJ stent through cystoscopy and stent was removed after 6 weeks with complete recovery. The success rate of ureteric fistula in our study was 100% which is comparable with other studies as well 20,25 . In our study, the most common cause of ureteric fistula was abdominal hysterectomy and same finding was seen in other study 25 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…One patient of ureteric fistula was managed by passing DJ stent through cystoscopy and stent was removed after 6 weeks with complete recovery. The success rate of ureteric fistula in our study was 100% which is comparable with other studies as well 20,25 . In our study, the most common cause of ureteric fistula was abdominal hysterectomy and same finding was seen in other study 25 .…”
Section: Discussionsupporting
confidence: 91%
“…Vesico-vaginal fistula was the most common type among all genitourinary fistulae accounting for 64-78% in various studies 20,21,22 .In our study the second most common type was uretero-vaginal fistula accounting for 10% of all varieties. Similar incidence was found in other study 20 .Priyadarshi et al quoted the frequency of uretero-vaginal fistula as 14% 21 . In our study vaginal route of repair was adopted in 46 (59.74%) cases and 28 (36.6%) had abdominal route of repair.…”
Section: Discussionsupporting
confidence: 53%
“…The current results were supported by Saaqib et al 7 who reported that Hydrotubation was shown to be successful in improving fertility in unexplained instances, and right shoulder tip discomfort was proven to be a statistically useful indicator for predicting pregnancy. They also stated that the majority of the patients conceived during the same cycle as hydrotubation.…”
Section: Group a Vassupporting
confidence: 80%
“…As well, our study was further supported by Prospective randomized controlled trial of Saaqib et al 7 compare the results of hydrotubation in cases of unexplained infertility in clomiphene citratestimulated cycles to the results of a control group (no Hydrotubation). The research involved 128 women, including 64 women in each of the experimental and control groups.…”
Section: Discussionsupporting
confidence: 58%